Assessment of wear properties of MWCNT and FA reinforced Al nanocomposites produced by powder metallurgy technique. (1st May 2019) - Udaya,; Fernandes, Peter
Abstract: Mono reinforced composites have limited capability in providing high specific strength and low wear rate. To vanquish the limitations, bi-reinforcements such as carbon nanotube (CNTs) and fly ash(FAs) were used in alumnium metal matrix. In this work wear and friction properties of composite fabricated by powder-metallurgy were investigated. It was found that CNT and FA reinforced aluminium composite (Al/CNT-FA) manifests improved tribological properties over unreinforced matrix material and mono reinforced composites. The worn surfaces reveal that the wear was governed by the combination of adhesive and abrasive wear mechanism.